Correction of Oblique-Angle Oscillation for Laser Doppler Vibrometry - Vladimir Kindl; Tomas Kavalir; Jiri Sika; Michal Krizek (Communications - Scientific letters of the University of Zilina, 2019)
The paper proposes a correction method of the oblique-angle vibration for laser doppler vibrometry. It briefly discusses the key mathematical approach considering the surface of the analysed object to be a reference plane and gives a practical example of the method proper application. The proposed correction method is practically verified by laboratory measurement of natural frequencies and mode shapes for vibrations of high voltage transformer housing. The results are further compared to equivalent accelerometer measurement.